Behavior Intention Penggunaan Digital Payment QRIS Berdasarkan Model Unified Theory of Acceptance and Use of Technology - Pamungkas, Yogi; Rahmayanti, Dewi (Jurnal Informatika Ekonomi Bisnis, 2024)
Indonesia is experiencing technological developments which can be seen from the increasing number of internet users. This technological development also occurs in the field of financial services or Financial Technology. This research aims to determine the behavioral intentions of the general public in Bengkulu in using digital payments called QRIS (Quick Response Code Indonesian Standard) with the Unified Theory of Acceptance and Use of Technology (UTAUT). The research method is quantitative using primary data whose population is the general public in Bengkulu with a sample of 102 respondents. Data analysis used the SPSS program multiple analysis method. The research results show that work expectations, business expectations, social influence, facilitating conditions, perceived value, and Personal Innovativeness influence the behavioral intentions of the general public in Bengkulu in using digital payments called QRIS. Furthermore, based on calculations, it is known that these 6 variables have a simultaneous influence of 98.3% on behavioral intentions. The remaining 1.7% is influenced by other factors not examined in this study.